THE RELATIONSHIP BETWEEN LEARNING SATISFACTION AND RE-PARTICIPATION INTENTION OF SENIOR LEARNING USING HAPPINESS AS A MODERATOR - Wang, Wan-Hui; Lin, Chin-Chiuan (International Journal of Application on Economics and Business, 2025)
The present study aims to investigate the relationship between learning satisfaction and re-participation intention of senior learning, and use the happiness as a moderator. A questionnaire survey was conducted, with the community in Tainan city, and the learner aged 55 and above were tested. Total of 521 questionnaires were sent out, and 486 valid questionnaires were received. Results of the present study found that there is a positive effect between the happiness and the re-participate intention. When the psychological and emotional happiness of the senior learner is higher, the re-participate intention also higher. The result indicates that improving seniors’ sense of happiness can enhance the promoting effect of course satisfaction on re-participation intention. When designing the senior learning courses, training institutions should not only focus on course quality and teaching effects, but also focus on improving learners’ sense of happiness. Paying attention to the psychological and social happiness of senior learners can promote they continue to participate in learning activities, thereby improving their overall quality of life and happiness.